Rejang Lebong District Students' Perception of Islamic Communication and Broadcasting Program IAIN Curup - Savri Yansah; Anrial Anrial; Nur Cholis (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
As the oldest study program, the Islamic Communication and Broadcasting Study Program as the oldest study program at IAIN is quite curvy, it must also improve the quality of both the facilities that support the activities of lecturers and students, including seeking to establish a broadcasting laboratory equipped with supporting tools, such as broadcasting for student practice, there is also Pesona FM radio where the broadcast is dominated by active KPI students. Other supporting elements are facilities that really help lecturers and students in broadcasting. However, in the last three years the number of KPI students has decreased, in 2019 there were (89) eighty-nine students, in 2020 (79) seventy-nine students and entering 2021 the number of KPI students has decreased, namely (50) fifty only students. In the last three years there has been a decrease in the number of students, so in-depth information is needed on this matter, so that it will be tested in the field on the perceptions of high school students on the same level about the IAIN Curup KPI study program. The method used in this research is qualitative research with an exploratory approach. The goal of exploratory research is to produce generalizations derived from inductive processes about the group, process, activity, or situation being studied. From the results of the study it can be described that the perceptions of high school students about the KPI study program are that they are generally not familiar with this study program and only a few students do, such as vocational students who do internships in the KPI study program, this is due to a lack of promotion and no KPI student activities like preaching to school before the previous Covid-19 pandemic.